2015
DOI: 10.1007/s13105-015-0394-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of changes in apelin receptor mRNA and protein expression in the myocardium and aorta of rats with two-kidney, one-clip (2K1C) Goldblatt hypertension

Abstract: Experimental and clinical evidences suggest that apelin and its receptor APJ are involved in the pathogenesis of cardiovascular complications. However, the role of apelin/APJ in hypertension is not sufficiently understood. Because chronic kidney diseases lead to hypertension and cardiac failure, we investigated the changes in apelin receptor gene expression in the myocardium and aorta of rat models of kidney disease hypertension. Two-kidney, one-clip (2K1C) hypertension was produced by placing a clip around th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Recent findings suggest that the apelin/APJ system may be involved in the pathophysiology of cardiovascular diseases . For the first time, Földes and colleagues reported that apelin may be involved in the pathogenesis of heart failure in the human .…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings suggest that the apelin/APJ system may be involved in the pathophysiology of cardiovascular diseases . For the first time, Földes and colleagues reported that apelin may be involved in the pathogenesis of heart failure in the human .…”
Section: Introductionmentioning
confidence: 99%
“…The skin and abdominal layers were sutured using 4-0 silk threads and 5-0 chromic catgut, respectively. 11, 12 After the animals recovered from the anesthesia, they were kept in individual cages under standard conditions. After 4 weeks, the 2K1C rats, along with the normotensive rats, were anesthetized using sodium thiopental (50 mg/kg, i.p.).…”
mentioning
confidence: 99%
“…Whereas the kidney plays a central role in the regulation of long-term blood pressure, aiming to improve this situation, the experimental model of renovascular hypertension has also been widely used [10].…”
Section: Introductionmentioning
confidence: 99%